The Potential for Controlling Maize Pest Spodoptera frugiperda (Lepidoptera: Noctuidae) Using Biological Agents Bacillus spp. - Muhammad Qoyyimul Amri; Yenny Wuryandari; Noni Rahmadhini (The University of Lampung, 2026)
Maize production is still facing many challenges nowadays. One of the main challenges in maize production is pest attacks. S. frugiperda has been causing significant damage to maize farming in Indonesia recently. This research was conducted to determine the potential of Bacillus spp. isolates Bcz-20 and Bcz-30 are identified as biological agent candidates to control the S. frugiperda population, with bacterial population densities of 109 CFU/mL, 108 CFU/mL, and 107 CFU/mL, respectively, as determined by in vitro and in vivo application tests. The Bcz-20 treatment with a population density of 107 CFU/mL was capable of suppressing the S. frugiperda larvae population in an in vitro application test, resulting in a mortality percentage of 47.5%. The Bcz-20 treatment with a population density of 109 CFU/mL was capable of suppressing the S. frugiperda larvae population by in vivo application test, resulting in a mortality percentage of 70 %. The conclusion, Bacillus spp. Bcz-20 isolates with a population density of 107 CFU/mL are efficient and effective for controlling the S. frugiperda larvae population.